Analisis Tingkat Perputaran Kas dan Perputaran Piutang Terhadap Profitabilitas Pada Koperasi SMA Negeri 5 Makassar - Suryani Harun; Renny Mointi; Meldilianus N.J Lenas (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2023)
This study aims to determine the analysis of the level of cash turnover and receivables turnover on profitability. There are 3 variables used, including the Free Variable (X1) cash turnover, the Variable (X2) receivables turnover and the Bound variable (Y) profitability using Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM). The results of this study prove that not always profitability can be generated from sales but the increase is caused by reduced debt and increased sales from decreasing assets moving to profit margins, but it can be said that all components in this study have a relationship, so it can be said that the Blessing Cooperative at SMA Negeri 5 Makassar experienced a profit surplus.